I’JAZ IQTISHADI INVESTASI DALAM PERSPEKTIF AL-QUR’AN - Winatun (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Islam encourages its followers to always strive for a good life, as a good life in this world is one of the supports for achieving a good life in the hereafter. One of the efforts to realize this is through investment activities. In the Qur'an, investment is considered essential for human welfare. The Qur'an provides basic concepts and principles for conducting investments according to Islamic teachings. Therefore, Islam emphasizes the importance of sharia principles in investing as a guide for society. Investment activities, both explicitly and implicitly, are included in several verses of the Qur'an and the Sunnah of the Prophet Muhammad (peace be upon him), who engaged in business and was an investment partner in Mecca from his youth until just before his prophethood. In Islamic economics, investment follows sharia regulations based on guidance from the Qur'an and Hadith. Sharia-compliant economic investment adheres to sharia principles, including prohibitions on usury (riba) and investing in unlawful businesses. It promotes transparency, relies on profit-sharing or sharia-compliant trade, and focuses on genuinely productive assets. Avoiding excessive speculation and adhering to national laws are essential for economic investment. Investment is defined as an effort to allocate funds with the aim of gaining future profits. Additionally, investment can be described as an asset or wealth management activity with a specific orientation, including strategies to achieve its objectives